Pirólise rápida de casca de soja: desenvolvimento do reator de leito fluidizado, análise do bio-óleo produzido e do vapor obtido na pirólise analítica - Oliveira, Tiago José Pires de (2015)
Environmental problems and climate changes due to global heating have happened by the emission of carbon dioxide, the gradual decrease of fossil fuels and the energy increasing demand have generated some interest by the development of a fuel safe source; thus the interest by sustainable and renewable energy sources has been growing. The main purpose of this present project has been a fluidized bed reactor conception and development to the fast pyrolysis of lignocellulosic biomass. In this project it has been presented and discussed the projects construction concepts, in addition to experimental tests conducted at the experimental unit aiming the fluidized bed reactor stable operation. The tests have enabled to identify the main problems, to analyze the causes and to propose solutions related to the reactor operation. These experiments have provided a better comprehension about the pyrolysis process, since the operational parameters control, equipment projects with considerable effectiveness until the overcoming of some important challenges to the conception of a new elaborated unit. The second unit has been in an initial tests phase and with some important parameters adjustments to the obtainment of bio-oil larger yield and improvement of the vapor condensing system. The experiments at the two prototypes have been conducted to 550 °C, to investigate the products composition obtained at the process, however only the bio-oil from the first prototype has been analyzed. The specific goals of this project have been to compare the composition of the vapor generated at the soybean hull analytic pyrolysis, using a commercial micropyrolyzer, with the bio-oil composition produced by an experimental unit in a fast pyrolysis fluidized bed reactor. The analytical pyrolysis experimental tests have been performed to the soybean hull at 450, 500, 650 and 750 °C. The pyrolytic vapors have presented more expressive contents of acetic acid, carbonic acid, limonene and hexadecane (450 °C); acetic acid, cyclohexane and tetradecane (550 °C); 1,3-pentadiene, limonene, hexadecane, tetradecane and oleanitrile (650 °C); 1,3-pentadiene, toluene, tetradecane and ethanedial (750 °C). The performance of acetic acid has decreased with the temperature increase. This fact is understood by the reaction of the acetic acid formation, which is less competitive under high temperature. The main bio-oil components have been analyzed at GC/MS and the results have indicated that this bio-oil may be used as an alternative source of chemical products with added value, because it is abounding in phenolic composts, which are used in the resin synthesis and in the pharmaceutical industry. Considering the products of prime pyrolysis reactions obtained at the analytical pyrolysis and the bio-oil which involves the vapor condensation and long length stays, an investigation about the extension of minor reactions may be held. The fast pyrolysis in bed reactors is subject to the occurrence of minor reactions. These reactions mainly occur due to important factors in the operation of these reactors, as the time of vapor retention, partial pressure, presence of minerals in the biomass and reaction temperature. Different temperature gradients in the fluidized bed reactor may also have contributed to the minor reactions events.